2015
DOI: 10.5194/acp-15-11399-2015
|View full text |Cite
|
Sign up to set email alerts
|

Natural new particle formation at the coastal Antarctic site Neumayer

Abstract: Abstract. We measured condensation particle (CP) concentrations and particle size distributions at the coastal Antarctic station Neumayer (70°39´ S, 8°15´ W) during two summer campaigns (from 20 January to 26 March 2012 and 1 February to 30 April 2014) and during the polar night between 12 August and 27 September 2014 in the particle diameter (Dp) range from 2.94 to 60.4 nm (2012) and from 6.26 to 212.9 nm (2014). During both summer campaigns we identified all in all 44 new particle formation (NPF) events. Fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 65 publications
(93 reference statements)
4
78
0
Order By: Relevance
“…As described in Weller et al (2015), NPF events at Neumayer showed generally almost comparable growth rates. Therein we 5 used a simple estimate, based on Nieminen et al (2010) and Yli-Juuti et al (2011) that demonstrated the need of other condensable vapours than sulfuric acid to sustain the observed particle growth (Weller et al, 2015).…”
Section: Npfmentioning
confidence: 78%
See 4 more Smart Citations
“…As described in Weller et al (2015), NPF events at Neumayer showed generally almost comparable growth rates. Therein we 5 used a simple estimate, based on Nieminen et al (2010) and Yli-Juuti et al (2011) that demonstrated the need of other condensable vapours than sulfuric acid to sustain the observed particle growth (Weller et al, 2015).…”
Section: Npfmentioning
confidence: 78%
“…Therein we 5 used a simple estimate, based on Nieminen et al (2010) and Yli-Juuti et al (2011) that demonstrated the need of other condensable vapours than sulfuric acid to sustain the observed particle growth (Weller et al, 2015). We employed now the same approach in connection with the NPF event at Kohnen (i.e.…”
Section: Npfmentioning
confidence: 99%
See 3 more Smart Citations